(untitled) (Research, Society and Development, 2022)
The aim of the study was to evaluate different diets for Apis mellifera in three regions of Santa Catarina, Brazil. The bees received the diets weekly, for 60 days. The treatments used and the corresponding crude protein contents were: D1 – sugar syrup; D2 – commercial feed (24.4%); D3 – sugarcane yeast + commercial sugar (17.0%); D4 – beer yeast + commercial sugar (14.9%); D5 – sugarcane yeast + textured soy protein + commercial sugar (20.9%). The parameters evaluated were: measurement of the breeding areas (drone, open, closed and total), measurement of the food deposit areas (honey and pollen) and percentage of infestation by Varroa destructor. At the end of study, a physical-chemical analysis of the honey was carried out. Significant differences were observed when comparing protein rations with the negative control group in the variables of areas of open brood, total brood (Sierra region) and infestation by Varroa destructor (Santa Catarina western and Sierra region). No changes were detected in the honeys in relation to the current regulations, demonstrating that the supply of the diets, under the conditions of the study, is safe for maintaining the standards of identity and quality of the final product.